Constitucionalización del derecho internacional de las inversiones: los casos de la expropiación indirecta y el trato justo y equitativo - Higa Silva, César (2013)
The purpose of this paper is to explore the impact of international investment law rules in the Economic Constitutional Law, especially those included in investment chapters of Peruvian’s Free Trade Treaties. In particular, it is expected to demonstrate the following (i) International Investment Law is part of Peruvian Legal System; (ii) provisions of these laws are mandatory and should be applied domestically; and (iii) interpretation and implementation of this legal right should be executed consistently with domestic legal system and Peruvian international obligations. This agreed Interpretation between Investment Law and Economic Constitution will have a positive effect in rationalization of public entities actions avoiding abuses and maltreatment to investors, in order to improve investment climate as a key element forachieving country’s sustainable development.